Organocatalytic Strategies for the Synthesis of Axially Chiral Compounds - Bencivenni, Giorgio (Synlett, 2015)
Atropisomers are compounds in which chirality arises from hindered rotation along the carbon–carbon or carbon–heteroatom single bond. Recently, organocatalysis appeared to be a rapid, valuable, and efficient strategy for their preparation in an enantioselective manner. In this report a general overview of the most important organocatalyzed atroposelective transformations will be given pointing out in particular the specific role played by the catalyst.1 Dynamic Kinetic Resolution2 Desymmetrization of Biaryls3 Direct Synthesis of Biaryls4 Asymmetric Friedel–Crafts Amination of Naphthols5 N-Alkylation via Phase-Transfer Catalysis6 Desymmetrization of N-Arylmaleimides
Keywords: atropisomers; organocatalysis; enantioselective synthesis; desymmetrization; dynamic kinetic resolution